[Namafjall From Above] - Streng, Evelyn Fiedler (1975)
Photograph of the Namafjall Area from above. The orange and white geothermal area is visible below, a small stream cutting through it. White steam shoots out of the plain throughout. A white bus is visible in the background ahead of a black plain covered in green grass. A group of people stand on a brown, rocky hill at the bottom of the photograph.